The Effect of Medical Hypnosis on Depression in the Elderly: A Case Report - Liko Maryudhiyanto (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction Depression in the elderly is a significant health issue requiring a holistic, bio-psycho-socio-spiritual approach. This report explores adjuvant medical hypnosis for severe depression in this population. Case: An 83-year-old male was diagnosed with severe depression without psychotic symptoms and mild cognitive impairment (HDRS 25, MoCA-Ina 21) after losing his wife and sibling. He was treated with Sertraline 25 mg and two sessions of medical hypnosis. Result: The patient showed significant clinical improvement; depressive symptoms reduced (HDRS 11), cognitive function improved (MoCA-Ina 25), appetite and sleep quality were restored, and suicidal ideation resolved. Discussion: Medical hypnosis, used synergistically with pharmacotherapy, can deliver comprehensive improvements across biological, psychological, social, and spiritual domains. This integrated approach successfully enhanced cognitive function and quality of life, highlighting its potential in geriatric psychiatry